Calcined chicken eggshell electrode for battery and supercapacitor applications. Issue 46 (27th August 2019) - Minakshi, Manickam; Higley, Stephen; Baur, Christian; Mitchell, David R. G.; Jones, Robert T.; Fichtner, Maximilian
Abstract : Biowaste eggshell can be used as a cathode while in its calcined form and it is found to be suitable as an anode in an electrochemical cell. Abstract : Biowaste eggshell can be used as a cathode while in its calcined form and it is found to be suitable as an anode in an electrochemical cell. This not only enables energy to be stored reversibly but also achieves waste management and sustainability goals by redirecting material away from landfill. Biowaste eggshell comprises 94% calcium carbonate (CaCO3 ; calcite), an attractive divalent ion source as a viable option for energy storage. X-ray diffraction and electron microscopy coupled with energy dispersive analyses of the calcined (thermally decomposed) biowaste eggshell show that CaO has been formed and the reaction is topotactic. Field emission scanning electron microscopy (FESEM) images of the textural relationship show that the thermal decomposition of calcite resulted in a change in morphology. High-resolution XPS spectra of the C 1s core level from the CaCO3 and CaO shows that there is a chemical difference in the carbon environments and the total atomic fraction of Ca for each sample with that of carbonate and oxygen varies. In a three-electrode configuration, a working electrode of CaCO3 is found to be electrochemically active in the positive region, whereas a CaO electrode is active in the negative region. This indicates the potential use of eggshell-derived materials for both cathode and anode. Both the electrodes exhibited a quasi-box-shaped potentiostatic curve implying a capacitor-type behaviour. The CaCO3 cathode possesses a modest discharge capacitance of 10 F g −1 but the CaO anode showed excellent capacitance value of 47.5 F g −1 . The CaO electrode in both positive and negative regions, at a current density of 0.15 A g −1 exhibited 55 F g −1 with a retention of nearly 100% after 1000 cycles. At a very low sweep rate of 0.5 mV s −1, the CaO electrode showed typical redox-type behaviour with well-defined peaks illustrating battery-type behaviour. The outcome of the calcite/CaO transformation, exhibiting technological importance for energy storage applications, may help to re-evaluate biowaste before throwing it away. The current work explores the viability of eggshell derived materials as a cathode/anode for use in batteries and capacitors.